2016
DOI: 10.1038/srep26282
|View full text |Cite
|
Sign up to set email alerts
|

An Atypical System for Studying Epithelial-Mesenchymal Transition in Hepatocellular Carcinoma

Abstract: Intrahepatic and extrahepatic metastases are frequently detected in hepatocellular carcinoma (HCC). Epithelial-mesenchymal transition (EMT) is believed to drive metastasis. There are not many well-established model systems to study EMT in HCC. Here we identified an atypical EMT while characterizing a population of mesenchymal cells in Huh7.5 hepatoma cell cultures. Cells with distinct morphology appeared during geneticin treatment of Huh7.5 cultures. Molecular characterization of geneticin resistant Huh7.5M ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 53 publications
1
12
0
Order By: Relevance
“…Out of this, 476 genes showed activation in Huh7.5M cells. This phenomenal regulation is in sync with the activation of HDAC 1 , 6 and 8 in Huh7.5M that we reported previously 24 .…”
Section: Resultssupporting
confidence: 89%
See 4 more Smart Citations
“…Out of this, 476 genes showed activation in Huh7.5M cells. This phenomenal regulation is in sync with the activation of HDAC 1 , 6 and 8 in Huh7.5M that we reported previously 24 .…”
Section: Resultssupporting
confidence: 89%
“…We previously reported that β-Catenin may not be a critical regulator of this EMT based on the absence of a credible change in β-Catenin levels between the two cells 24 . Contradicting this hypothesis, IPA of the transcription profiles flagged a highly active Wnt/β-Catenin signaling in Huh7.5M cells based on the upregulation of majority of its receptors and ligands (Fig.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations